THE IMPACT OF SUPPORTIVE MANAGEMENT ON THE EMPLOYMENT OF INTELLECTUAL CAPITAL-AN APPLIED STUDY IN A SAMPLE OF IRAQI BANKS - Lecturer Balsam Hussain Raheef; Lecturer: Dr. Lawhedh Khaleel Ibrahim (Scholars Digest Publishing, 2025)
The current research aims to demonstrate the impact of supportive management with the following dimensions) Psychological and social support, safe and supportive work environment, effective communication, motivation and appreciation) The research was based on a main hypothesis (the existence of a significant impact of supportive management on the dimensions of intellectual capital for the sample banks). The research used the descriptive, historical, analytical, quantitative and statistical method and adopted the questionnaire as a tool to collect data and information from the sample of (40) who occupy the positions of (authorized manager, M. Commissioner Director, Department Director, Department Director, M. Department Director, Division Director, Division Officer, and Unit Officer) Relying on the statistical program (SPSS) to calculate (arithmetic mean, standard deviation, coefficient of variation, F test, coefficient of determination R2, , and T test) we can confirm that these results show a significant and positive correlation between supportive management and the dimensions of intellectual capital (human, structural, and relational), with high statistical significance. The research was divided into four sections: - The first section: Methodology of the research, and the second research: The first section dealt with the research methodology, the second section dealt with the basic concepts of the research, and the third section dealt with analyzing the results of the research: Analyzing the results of the research and testing its hypotheses: The fourth section emphasizes the most important conclusions and recommendations reached by the research.